Development of a multipurpose scaffold for the display of peptide loops. Issue 6 (24th April 2017) - Rossmann, Maxim; J. Greive, Sandra; Moschetti, Tommaso; Dinan, Michael; Hyvönen, Marko
Abstract: Protein–protein interactions (PPIs) determine a wide range of biological processes and analysis of these dynamic networks is increasingly becoming a mandatory tool for studying protein function. Using the globular ATPase domain of recombinase RadA as a scaffold, we have developed a peptide display system (RAD display), which allows for the presentation of target peptides, protein domains or full-length proteins and their rapid recombinant production in bacteria. The design of the RAD display system includes differently tagged versions of the scaffold, which allows for flexibility in the protein purification method, and chemical coupling for small molecule labeling or surface immobilization. When combined with the significant thermal stability of the RadA protein, these features create a versatile multipurpose scaffold system. Using various orthogonal biophysical techniques, we show that peptides displayed on the scaffold bind to their natural targets in a fashion similar to linear parent peptides. We use the examples of CK2β/CK2α kinase and TPX2/Aurora A kinase protein complexes to demonstrate that the peptide displayed by the RAD scaffold can be used in PPI studies with the same binding efficacy but at lower costs compared with their linear synthetic counterparts.